Development of E-Module based on Flipbook Learning Model Problem Based Learning (PBL) to Improve Critical Thinking Ability - Iza Alfi Rohmatin; Arimbi Racmayani; Jumadi Jumadi (Universitas Lambung Mangkurat, 2022)
This paper aims to develop a flipbook-based physics e-module to determine students' critical thinking skills by applying the problem-based learning (PBL) model. The method in the 4-D model research is qualitative descriptive. The research using a non-probability sampling technique that is selected is subject class 10 MIPA MAN 4 Bantul. Techniques for collecting data with test instruments and indicators are used in critical thinking, namely analyzing facts, formulating problems, selecting, clarifying and evaluating arguments logically, and drawing conclusions. The media and material analysis results show that the category is feasible, with a percentage of 85.43 and 75.41. The E-Module shows the average response in education suitable for use on critical thinking skills. The normality value of the control class is 0.002, and the experimental class 0.156. The homogeneity of the statistical significance level is 0.304. Therefore, the data has met the requirements to be tested using an independent test; there is a significant difference between the control class with lectures and experiments using e-modules.